ANALISIS LATAR SEBAGAI ATMOSFER DALAM CERPEN ”AKU PRIMADONA” KARYA YATTI SADELI - Oktapiani, Anisa; Lestari, Riana Dwi; Rosi, Rosi (IKIP Siliwangi, 2019)
The purpose of this study is to (1) analyze the background in the short story